From the Institutional Repository to a CRIS system - Fernandes, Sofia; Pinto, Maria João (Qualitative and Quantitative Methods in Libraries; Vol 7 No 3 (2018): September 2018 Issue, 2019)
This article intends to present and reflect on the challenges of adopting a current research information system (CRIS) with the existence of an institutional repository (IR). Higher education institutions, and its research centers, are facing increasingly needs to obtain information on the research undertaken and their results and performance. Most of the times, the answer has been given partly from the IR. The aggregation and availability of publications in one single place has helped to respond more easily to internal issues and external demands from evaluation and funding agencies, especially regarding open access publications. However, needs have increased: research centers and higher education institutions need relevant information for strategic decision-making and guidance in such demanding times. Besides, institutions and researchers must be very responsive to the open access challenges brought by national policies. This study pretends to share and analyze the main challenges that must be aware when adopting or implementing a CRIS if the community has already an IR. The main concerns relate mainly to technological issues of interoperability that will make life easier for researchers: to deposit once and to reuse multiple times. There are also challenges in terms of the continuity of the repositories that will have to reinvent themselves in this new context. Raising awareness and training issues for researchers and modeling processes at the institutional level are also important in facilitating the research management process and delivering successful results for the institution.